Enhancing the Signal-to-Noise Ratio of Astronomical Images with a Charge Injection Device - Foadi, Raad Falih Hassan (Iraqi Journal of Science, 2025)
The signal-to-noise ratio of the Charge Injection Device is considered the most critical factor for evaluating the quality of the Charge Injection Device (CID). CID produces unwanted signals (noise) that can obscure the signal that needs to be detected. Noise is an essential obstacle for spectral identification of the observed object because it generates a fluctuation that can surpass the signal level. Therefore, reducing noise is very important to get a high-quality image. There are three main types of noise in the CID camera system: shot noise, readout noise, and dark current noise. The readout noise has the highest impact on the astronomical image because this noise is caused by a variety of factors, including trapping-state noise, reset noise, background noise, charge-transfer noise, and output amplifier noise. In order to reduce the readout noise and enhance SNR, non-destructive readout (NDRO) and binning techniques are used. This work examines the SNR of astronomical images with CID820 using NDRO, the binning process, and compound images. The study deals with three cases: the first is calculating SNR using different values of NDROs without binning. The second case uses different values of NDROs with 2, 4, and 6 binning. The third case involves combining two or more astronomical images to increase the SNR of CID820. Finally, the study compares the output results of SNR for the three cases to decide which case is the best for astronomical imaging using CID820.